Home Remedies for Prevention and Curing of Cancer - Lawrence Mary. K, Sivaranjani. K, Rajeswari. P; Lawrence Mary. K, Sivaranjani. K, Rajeswari. P (International Journal of Advanced Science and Technology, 2020)
Traditional cancer-fighting food could lower the risk and prevention of cancer. Calories and nutrients are mostly preferred to stay healthy. Proper nutrition can aid humans to be reliable. Many customary home remedies have forgotten by future cohorts are reminded by Black cumin seeds, turmeric, South Indian Soup (Rasam), thiripala, carrot, NithyaKalyani, and citrus fruits. This paper provides some glimpse of organic remedies that connects oneself with nature without loss. The World Health Organization’s International Agency for Research on Cancer (IARC) clarifies food and drink contains carcinogen would cause cancer. It also recommended Vitamin C with rich anti-oxidant foods will prevent and cure significant cancer cells. This review is an attempt to shed light on some of the healthy home foods to heal and assists humans to lead a sturdy, balanced life.